Editorial: Harnessing the Power of Interprofessional Practice and Education to Meet the Multi-Faceted Needs of Individuals with Intellectual Disability - Giess, SallyAnn (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Editorial